ANALISIS KUALITAS SUMBER DAYA MANUSIA DAN PELAYANAN PENYEDIA JASA ANGKUTAN TERHADAP PENGIRIMAN SEMEN DI PT CIPTA MORTAR UTAMA - Supriyadi Supriyadi; Agus Hermawan (SMART Management Journal, 2022)
This study aims to determine the analysis of the quality of human resources and services of transportation service providers on the delivery of cement at PT. Cipta Mortar Utama. The data in this study are primary data obtained from in-depth interviews and then the results of in-depth interviews are used as questionnaires to be discussed further by respondents consisting of transportation drivers who are in charge of sending goods. This type of research is qualitative research using SWOT analysis. This research was conducted using a sample of 36 respondents. Based on the results of in-depth interviews with indicators from each variable, 60 questionnaire questions were obtained with the classification of strengths, weaknesses, threats, and opportunities, calculated the results of the analysis, it was concluded that the analysis of the quality of human resources and transportation service providers for cement shipments at PT. Cipta Mortar Utama, is in Quadrant I (Aggressive).